Generation of Longitudinal Bessel Beam Based on Complex Amplitude Metasurface - Lei Zhang; Qiang Jiang; Xuedian Zhang; Songlin Zhuang (Photonics)
Bessel beams occupy an important position in optical research due to their characteristics of long focal depth, self-healing ability, and diffraction-free propagation. Traditional methods for generating Bessel beams suffer from complexity, a large size, low uniformity, and limited NA. Metasurfaces are considered to be a new technology for the miniaturization of optical devices due to their ability to regulate optical fields at subwavelength scales flexibly. Here, we generated Bessel beams by a complex-amplitude (CA) metasurface. The polarization conversion efficiency was controlled by the geometric size, while the phase value from 0 to 2π was manipulated based on the Pancharatnam–Berry (PB) phase. This approach enabled precise control over the axial intensity distribution of the optical field, which facilitated the generation of sub-millimeter-scale Bessel beams. Axial light field control based on CA metasurfaces has great potential for applications in a variety of fields, such as particle manipulation, large-depth-of-field imaging, and laser processing.